MEMBANGUN HUBUNGAN SEKOLAH-RUMAH TERHADAP KETERAMPILAN BERBICARA SISWA SEKOLAH DASAR: Kajian Literatur - Aulina Roudlotul Jannah; Riyadi, Arie Rakhmat; Neni Maulidah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Speaking skills are a fundamental aspect of academic and social development in elementary school students, especially at the lower grade level. However, various internal and external obstacles—such as low self-confidence, limited Indonesian vocabulary, and the dominant use of local languages at home—hinder the optimal development of children's speaking abilities. This study aims to analyze the relationship between school-home collaboration and students’ speaking skills through a literature review. The method employed is library research with a descriptive qualitative approach, grounded in constructivist philosophy and Epstein’s theory of parental involvement. The findings reveal that speaking skills develop more effectively within an educational ecosystem that consistently supports verbal interaction both at school and at home. Harmonious educational relationships between teachers and parents—through activities such as shared reading, family discussions, and regular communication between home and school—significantly enhance children's ability to express ideas. Furthermore, culturally contextualized learning and inclusive communication strategies are key to overcoming challenges posed by the use of local mother tongues. Thus, building a synergistic school-home partnership grounded in local values is an effective strategy for fostering students’ speaking skills in a sustainable manner.